Legal Analisys of The Use of Telemedicine In Tradisional Based on The Perspective of Health Law No 17 of 2023 - Suparna, I Ketut; Kuswardhani, R.A. Tuty; Hartawan, I Gusti Agung Gede Utara; Widyantara, Made Oka (Journal of Law, Politic and Humanities, 2025)
The advancement of information and communication technology, particularly telemedicine, has transformed the healthcare sector, including its application in traditional medicine in Indonesia. Traditional medicine is recognized under Law No. 17 of 2023 concerning Health; however, the implementation of telemedicine in this field has not yet been specifically regulated. This study aims to analyze the legal aspects of using telemedicine in traditional medicine based on the aforementioned Health Law. The research method employed is normative legal research using statutory and conceptual approaches. The findings reveal several challenges, including regulatory gaps, standardization issues, patient data protection, and practitioner competence. Although the Health Law provides a general legal framework, specific regulations regarding the use of telemedicine in traditional medicine are still lacking. The study concludes that additional regulations are needed to govern the use of telemedicine, ensure quality control, protect patient rights, and certify practitioners. The recommendations include drafting specific regulations, enhancing practitioner competence, and increasing public education to ensure the safe and effective implementation of telemedicine in traditional medicine.